(untitled) (Fiep Bulletin - online, 2014)
The objective of this study was to analyze the kinematics characteristics of children’s gait in the aquatic environment. The march was described through the angular displacement of the knee and ankle and a qualitative analysis. The study happened in the swimming pool of the CEFID-UDESC, where four children of both the sexes with age varying between 7 and 12 years participated. The children had carried through 12 passages in one footbridge of 5 meters of length in a self - selected speed. The immersion level was in the manubrium for child number 2, in the 7th rib for child number 3, in the xiphoid process for child number 1 and in the 12th rib for child number 4. The children had only been filmed in the left side in the sagittal plan with a digital camcorder that was in a sealed box located at 3,6 meters of the footbridge in a height of 0,57 meters. For the analysis of the angular displacement had been marked the following anatomical marks: greater trochanter of femur, tibial plateau, lateral malleolus and fifth metatarsal head. For the analysis of data a descriptive statistics. The achieved data in this study had been compared with the found ones in literature referring to the terrestrial environment. It was possible to observe that the biggest alterations had occurred during the phase of initial contact, the ankle met plain and the knee in bigger flexion that in the terrestrial environment. Of the four arcs of movement of the ankle and the knee, only 3 had been evidenced. Based on this analysis when prescribing the trainings of gait in the aquatic environment it is important to establish the objective of the rehabilitation at short, medium and long term to control some variable that influence in the movement as the level of immersion.